The Factors Influencing Banks' Risk-Taking Behavior: Evidence from The Turkish Banking Industry - Yüksel Aydın; Erdal Demir (Ekonomi, Politika & Finans Araştırmaları Dergisi, 2025)
This article empirically analyzes the factors affecting the risk taking of commercial banks in Turkey for the period 2010-2023. Inverse Z score was utilized as a measure of bank risk taking in the developed panel data regression models, while various bank-level and macro-level variables were employed as independent variables. The developed models in this article is estimated separately for the main sample including all banks and the sub-samples formed. According to the results, bank size, bank capital, bank deposit and net interest margin variables tend to reduce the level of bank risk taking in terms of the main sample. However, liquidity risk, credit risk, inflation rate, economic growth and the COVID-19 pandemic crisis tend to increase the level of bank risk taking. Findings from subsamples of listed, non-listed, domestic and foreign banks indicate that bank size, bank capital and net interest margin tend to reduce the level of bank risk taking, which supports the findings from the main sample. Finally, the results of this article have important implications for bank management, regulatory mechanisms and policy makers in terms of controlling the risk-taking behavior of banks, ensuring stability in the banking sector and building a sustainable banking sector.